A single‐stage integrated bridgeless AC/DC converter for electrolytic capacitor‐less LED lighting applications. (31st March 2014) - Ma, Hongbo; Zheng, Cong; Yu, Wensong; Lai, Jih‐Sheng (Jason)
Summary In this paper, a single‐stage integrated bridgeless AC/DC converter is proposed. As compared to its counterpart that is composed of totem‐pole boost power factor correction (PFC) cascade fly‐back DC/DC converter, the studied circuit has less components number while overcoming the limits of the totem‐pole type. Thus, it is suitable to the low‐power LED lighting applications. Furthermore, when both PFC inductors Lb and magmatic inductance Lm of the transformer TR1 operate at discontinuous current mode, the bus voltage vCB can be used to decouple the ac input and constant dc output power. Thus, the approach of increasing bus voltage ripple is employed to eliminate electrolytic capacitors and obtain long operation lifetime. Additionally, it is able to be compatible with our studied twin‐bus configuration for increasing the overall efficiency. A 50‐W hardware prototype has been designed, fabricated, and tested in the laboratory to verify the proposed converter validity. Copyright © 2014 John Wiley & Sons, Ltd.